The Kansas Beef Cattle Improvement Program - H.W. Westmeyer; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1968)
The Kansas Beef Cattle Improvement Program is to help improve beef cow herds in Kansas and to provide information that will be valuable to producers in selecting breeding animals and making management decisions. The program is not to encourage competition among herds. Environmental conditions vary from herd to herd so competitive among herds cannot be "under the same rules".
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Management; Environment conditions; Performance